Ubuntu e Paulo Freire: percursos da afroperspectividade para uma educação descolonizadora - Oliveira, Daniela Pinheiro de (2024)
Based on modern European thought, Western philosophy built up a self-image of universal thought and, as a result, produced a recurring delegitimization of the knowledge produced on other continents, especially knowledge from Africa, the cradle territory of humanity and culture, whose countless peoples were subjected to colonial slavery and neo-colonial servitude for around four centuries. Because of this, colonial processes, which still persist, especially in the symbolic sphere, constitute institutional mechanisms that, in turn, marginalize, make invisible and oppress other coexisting forms that differ from the hegemonic and normative model of the West, whose premise is the maintenance of this logic in the various spheres of Brazilian, African and Latin American social reality. Therefore, this debate is vitally important for the daily practice of education that values the plurality of knowledge and the possibilities of epistemic decolonization, in order to enrich the various ways of dealing with the world and with others. This study focuses on the possible dialogues between Ubuntu Philosophy and Paulo Freire's philosophical-pedagogical proposal, particularly with regard to the emancipatory potential of these humanistic conceptions.The thesis is therefore presented with the aim of examining, on the one hand, the Ubuntu Philosophy, in its Bantu African cosmoperception, based on the concern both of the individual with the collective and of the collective with the individual, and, on the other hand, Paulo Freire's dialogical pedagogy, which is part of the concept of education according to which nobody educates anyone, nor does anyone educate themselves, since people educate themselves in communion, mediated by the world. To this end, we started with the following question: "Is it possible to establish a dialogue between Ubuntu and Paulo Freire's thought that allows us to carry out a practice for decolonizing education?" To answer this question, we developed an analysis guided by African, Afro- American and Latin American decolonial theorists, among whom the following stand out: Paulo Freire, Renato Nogueira, Mogobe Ramose, Frantz Fanon, Oyěwùmí. This work started from the hypothesis that there are profound conceptual correlations between Ubuntu ideas and conceptions and Freirean ideas and categories, which contribute to enhancing the processes of decolonization of traditional and modern educational conceptions and practices, in order to propose pluriversal paths and emancipatory and anti-racist pedagogical practices, both in the classroom and in other educational spaces. From a methodological point of view, the thesis is developed through a qualitative conceptual approach, with a bibliographic focus. The analysis produced confirms that the ubuntuistic pedagogical praxis is a cognitive foundation in which studies and science, based on African epistemologies, are a counter-colonial instrument, assuming an Afro-perspectival identity. A praxeological foundation whose meanings are perceived in Paulo Freire's thought, it reaches out as an intervention in educational praxis, in collective pedagogical action with the pluriversality of other epistemologies; after all, the production of knowledge has no demarcated place, because philosophies are produced everywhere in the world.